Temperature imaging during the hydrogen release reaction from a liquid organic hydrogen carrier (LOHC) system using phosphor thermometry - Bollmann, Jonas; Bauer, Florian; Keim, Silvan; Herz, Nikolas; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (Experiments in Fluids, 2024)
Liquid organic hydrogen carrier (LOHC) systems offer a particularly interesting option for chemical hydrogen storage. In order to characterize and understand the endothermal hydrogen release from the carrier liquid and to evaluate suitable catalyst materials, knowledge of the temperature fields in the dehydrogenation reactor is important. One suitable technique for planar temperature sensing in reacting systems is phosphor thermometry. It is based on the excitation of a luminescent material by a laser pulse and detection of the subsequent phosphorescence signal. We investigated the luminescence of the thermographic phosphor (Sr,Ca)SiAIN3:Eu2+ (“SCASN:Eu2+”) dispersed in the H0-DBT / H18-DBT LOHC system in a temperature range from 400 to 600 K. A measurement cell enables repeatable and homogeneous measurement conditions of the hydrogen release reaction. A catalytic plate was put inside the heated LOHC. Temperature fields during the hydrogen release reaction were measured for the first time using the phosphorescence decay time (PDT) and the phosphorescence intensity ratio method (PIR). As expected, a strong cooling at the catalyst surface during the endothermal hydrogen release reaction could be observed, which was quantified to be in the range of 40 K. Graphical abstract: (Figure presented.).
CRIS-Team Scopus Importer:2024-08-23